DETERMINANT WHOSE ELEMENTS ARE SYMMETRIC FUNCTIONS - Trenčevski, Kostadin G.; Risteski, Ice B. (Matematichki Bilten, 2001)
In this paper is given one theorem of the “small” generalized Vandermonde determinant.